PENGURANGAN DEFECT PADA PRODUK SEPATU DENGAN MENGINTEGRASIKAN STATISTICAL PROCESS CONTROL (SPC) DAN ROOT CAUSE ANALYSIS (RCA) STUDI KASUS PT. XYZ - Moch. Teguh Fajrin; Wiwik Sulistiyowati (Universitas Ahmad Dahlan Indonesia, 2018)
PT. XYZ is a foreign capital investment companies are located in one area of town of Sidoarjo which has more than 7000 employees in it and of course want to have a high quality product . PT footwear products. XYZ is the world quality products that promote the quality and comfort of the wearer. Problems that occur in the production process of PT . XYZ of 7 -injection engine that has the most number of engine defect is 5.6 and 7. Quality products at heavily influence the shoe production to consumers. If damaged, then the product can not be distributed to consumers .Therefore , the quality of the shoes must be maintained for the successful marketing of the product. From our previous improvements made in reducing the defect in the production process , but the result is less than optimal , so do research that aims to make improvements again with another method . The method used in this research is to apply the methods of Statistical Processing Control (SPC) and Root Cause Analysis (RCA). The results of the check sheet analysis and Pareto diagram can be seen the frequency of product defects (defects) over roughing most occurred in March 2016 as many as 345 shoes (62%) of the total production of 489 products. Then the second frequency in February 2016 as many as 214 shoes (38%) of the total production of 357 products. And from the image Control Chart P can be concluded that the data are in a state of uncontrolled. Because of all these 50 data, there is one data point that is outside the control limits (out of control), on the 4th point the data has a value of the proportion of 1, beyond the limits Upper Control Limit (UCL) is equal to 0.938. During the dots located within the boundaries of a controller, a process is under controlled conditions, and no action required. However, one point that lies outside the control limit is interpreted as the fact that the quality control in the production process (injection) PT. XYZ uncontrolled or still experiencing irregularities. Whereas the causes of the failure of a critical process in the production process are humans, machines, methods and materials.